2018
DOI: 10.3390/molecules23061469
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferation Effect of Theasaponin E1 on the ALDH-Positive Ovarian Cancer Stem-Like Cells

Abstract: Ovarian cancer has the highest mortality rate of all gynecological malignancies and the five-year death rate of patients has remained high in the past five decades. Recently, with the rise of cancer stem cells (CSCs) theory, an increasing amount of research has suggested that CSCs give rise to tumor recurrence and metastasis. Theasaponin E1 (TSE1), which was isolated from green tea (Camellia sinensis) seeds, has been proposed to be an effective compound for tumor treatment. However, studies on whether TSE1 tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In the current study, we showed that the protein expression level of putative stem cell markers, such as Nanog and BMI1, is increased in ALDH-positive sorted cells compared with ALDH-negative cells. This finding is in agreement with other reports [ 35 , 36 , 37 ]. For example, Yu et al [ 35 ] reported that the mRNA levels of BMI1 and Snail were significantly elevated in ALDH-positive head and neck squamous cell carcinoma (HNSCC) cells.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, we showed that the protein expression level of putative stem cell markers, such as Nanog and BMI1, is increased in ALDH-positive sorted cells compared with ALDH-negative cells. This finding is in agreement with other reports [ 35 , 36 , 37 ]. For example, Yu et al [ 35 ] reported that the mRNA levels of BMI1 and Snail were significantly elevated in ALDH-positive head and neck squamous cell carcinoma (HNSCC) cells.…”
Section: Discussionsupporting
confidence: 94%
“…This finding perhaps indicates that Pt412 would be quicker to develop ALDH conferred chemoresistance and relapse as their corresponding spheroids were simulated to reach their putative nutrient and space limitations fastest. Given that Pt412 contains the highest proportion of ALDH+ cells, which are generally more proliferative and chemoresistant [32], [87], [88], this observation is plausible. Additionally, this interpretation supports our in vivo evidence showing that xenograft tumors generated from Pt412 spheroids reached the tumor size endpoint 1 week faster for P0 and P3 and 2 weeks faster for P6 than tumors generated from Pt224 spheroids.…”
Section: Discussionmentioning
confidence: 96%
“…However, a substantial number of compounds studied in the timeframe of this review acted via mechanisms similar to those described previously (Podolak et al 2010). These include a decrease of cell membrane permeability (Lorent et al 2013(Lorent et al , 2016Nishimura et al 2021), inhibition of angiogenesis (Hong et al 2013;Guan et al 2015), sensitization of cancer cells to chemotherapeutics (Deng et al 2017;Shen et al 2017;Chen et al 2019b;Guo et al 2019), or inhibition of cancer cell migration (Jiang et al 2017;Jia et al 2018). An interesting example of the latter is a modification of the aquaporin water channel by some triterpene saponins (Pan et al 2012;Nakhjavani et al 2019).…”
Section: Mechanisms Of Cytotoxic Impact On Cancer Cells In Vitromentioning
confidence: 99%